Klasterisasi Penggunaan Ban dengan Cost Per Kilometer Terendah pada PT. PL menggunakan Metode K-Means - Syani, Muhammad; Tundo; Sugiyono; Wahyudi, Tri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Established in 1969, PT. Puninar has grown to become one of Indonesia's leading logistics companies. The company provides a broad range of logistics solutions through its subsidiaries, encompassing material management, manufacturing, warehousing, distribution, customs services, freight forwarding, and post-delivery operations. After fuel, tires represent the second-largest expenditure for the company. Proper tire management can reduce maintenance costs, making it a key cost-reduction strategy in the logistics sector. This study utilizes data mining techniques, specifically the K-means method, to analyze and classify tires based on travel distance and the lowest cost per kilometer, enabling monthly cost monitoring. PT. Puninar allocates approximately two billion rupiah per month for tire inventory due to its fleet of over seven hundred trucks. The company currently employs various tire brands, including Bridgestone, Doublecoin, Effiplus, Chengsang, and others, with varying levels of durability.